الأستاذ قاسم أحمد في ضوء كتابه "العودة إلى القرآن": دراسة نقدية = Kassim Ahmad in the light of his book "The Return to the Qur’an” critical study - Al-Khayrabadi, Mohammed Abul Lais (The Institute of Hadith Research (INHAD, Malaysia), Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
الأستاذ قاسم أحمد من مواطني ماليزيا، وهو أول من أتى بفكرة الاكتفاء بالقرآن وبلفظ آخر "فكرة القرآنيين" إلى ماليزيا، وكتب كتابا سماه "العودة إلى القرآن" داعيا به إلى أن القرآن كاف، ولا حاجة إلى السنة، وادَّعى أن أول من استحدث فكرة مصدرية الحديث وحججه هو الإمام الشافعي (ت204ﻫ)، وفنَّد هذه الفكرة، وادعى أن الحديث نشأ نتيجةً للصراعات السياسية الدينية خلال القرنين الأول والثاني، إما تأييداً لآراء الطوائف المتناحرة، أو قضاءً على الطائفية السياسية الدينية، ويرى أن للسنة آثارا سيئة على الأمة، ثم أتى بشبهات داعمة لرفض الحديث، ثم ذكر لمنهجية التفسير العلمية تسع قواعد، فهذه الورقة تحاول أن تعرض أفكاره بكل الشفافية، ثم يقوم بالرد على أفكاره ردا علميا. ********************************************************** Kassim Ahmad is Malaysia’s foremost thinker and writer, he is the first Malaysian thinker that comes up with the idea of sufficiency of the Qur’an or we call it as Quranist Movement. He wrote the book called “The Return to the Qur’an” which is promoting the idea of Quranism that holds the Qur’an to be the most authentic criterion in Islam and rejects the religious authority, realibility and authenticity of the Hadiths collections and challenges the infallibility of the purported words of Prophet Muhammad s.a.w. He claimed that Imam As-Shaafei is the first Muslim scholar that introduced the idea of religious authority of Hadith and legitimate form of source for deriving Islamic law. He refuted this idea and claimed that the discussion arose as a result of religious political conflicts during the first and second centuries, either to support the opinions of the rival factions or in the elimination of religious political sectarianism. Kassim Ahmad believes that the Sunnah has a bad effects on the Muslim community and then he came to support this idea with the suspicions and criticism to the hadith. Finally, he introduced the nine rules related to the scientific methodology in Qur’anic Interpretation. This paper tries to present his ideas with all transparencies, and then respond to his ideas through scientific response.